Development of Inclusive Education Competencies Through In-Service Teacher Training – Analysis of the Programs of Continuing Education Institutions, Human Resources - Daniela Ionescu; Ecaterina Vrăsmaș (Educaţia 21)
In contemporary education, teacher training from an inclusive perspective must address various factors, including educational policies and theoretical frameworks. As the significance of inclusion in education grows, the number of training programs focused on this perspective is expected to rise, a trend supported by studies in Romania over the past decade. This study aims to determine changes in the number, formats, and content of inclusive education training programs organized between 2017 and 2022, proposed for 2022-2023, and accredited nationally. We analyzed documents comprising approved/accredited training programs for teachers. Using broad inclusion criteria, 41 data were requested, and we received 21 completed, which were eligible for analysis, covering 48 accredited and 5 complementary training programs. Our findings indicate no positive percentage variation in the number of inclusive education training programs, the average number of participants, or the number of programs including subjects adjacent to inclusive education, despite the diverse profile of trainers. The national offering is consistent, and many teachers have already completed such programs. In the first stage, information was collected on both the formal (name, accreditation order, type of program, number of hours) and practical (regional or national, complementary or accredited). Documents from national and international organizations involved in this field were also consulted. The results suggest that, despite the consistent offering of inclusive education training programs, there has been no significant increase in the number of these programs or participants, indicating the need for further improvements to more effectively achieve the goal of training teachers in inclusive competencies.